STUDI PENGOMPOSAN LUMPUR HASIL PENGOLAHAN LIMBAH CAIR PT INDOFOOD CBP DAN LIMBAH BAWANG MERAH GORENG MENGGUNAKAN AKTIVATOR EM4 DAN LUMPUR AKTIF - Dewi Anggraeni (Jurnal Teknik Lingkungan, 2012)
Sludge from food industry potentially treated with the composting methods because of any organic matter such as carbohydrates, proteins, fat, coarse fiber, water and macro nutrients such as nitrogen and phosphorus. This research had been conducted composting process that sludge mixed with fried onions. Composting process used two activators. They are Effective Microorganisms 4 (EM4) and activator from activated sludge. Compost matured have meet the requirements of SNI 19-7030-2004. The best result at variations on activator em4 with  ratio sludge : fried onion = 9 : 1 with result C-organic 12.84%, N-total 0.84%​​, 0.49% P-total, K-Total 0.27% and the C/N ratio 15.31. In the activator of activated sludge with same variation showe the results C-organic 13.06%, N 0.76%, P 0.53%, K 0.33% and C/N ratio 17.13.